Complexity in Classroom Foreign Language Learning Motivation A Practitioner Perspective from Japan - Sampson, Richard J. (Second Language Acquisition, 2016)
This book explores how complex systems theory can contribute to the understanding of classroom language learner motivation through an extended examination of one particular, situated research project. Working from the lived experience of the participants, the study describes how action research methods were used to explore the dynamic conditions operating in a foreign language classroom in Japan. The book draws attention to the highly personalised and individual, yet equally co-formed nature of classroom foreign language learning motivation and to the importance of agency and emotions in language learning. It presents an extended illustration of the applicability of complex systems theory for research design and process in SLA and its narrative approach shines light upon the evolving nature of research and role of the researcher. The study will be a valuable resource for practitioners, researchers and postgraduate students interested in classroom language teaching and learning, especially those with a focus on motivation among learners